Pengaruh Kualitas Produk, Harga Dan Brand Image Terhadap Keputusan Pembelian Wardah (Study Kasus Mahasiswi Pada Prodi Manajemen Universitas Dehasen Bengkulu) - Efendi, Fithria Habib; Susena, Karona Cahya; Rahman, Abdul (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
A consumer in buying an item often assesses whether or not the item is suitable for them, whether or not it is suitable for them, therefore consumers really prioritize choosing by looking at product quality, price, and brand image to fulfill their wants or needs in buying goods.The purpose of this study was to determine the effect of product quality, price, and brand image on Wardah purchasing decisions for students in the Management Study Program at Dehasen University Bengkulu. The type of research used is quantitative. The data analysis methods used are validity test, reliability test, multiple linear regression, cyclical test, hypothesis test, and determination test The results of multiple linear regression have the equation Y = 22.500 + 0.302X1 + 0.017X2 + 0.923X3 + 3.250, because the direction of regression is positive, it means that if the product quality, price, and brand image increase, the decision to purchase Wardah products for students in the Management Study Program of Dehasen University Bengkulu will also increase. Product quality has a significant effect on purchasing decisions for Wardah products for students in the Management study program of Dehasen University Bengkulu, this is proven by the results of the t test which shows that the tcount value is smaller than the t table (3.376> 1.671) with a significant value of 0.001 <0.05, meaning that H0 is rejected Ha is accepted. Price has a significant effect on purchasing decisions for Wardah products for students in the Management study program at Dehasen University Bengkulu, this is evidenced by the results of the t test showing the tcount is greater than the table (0.183 < 1.671) with a significant value of 0.855> 0.05, meaning that H0 is accepted and Haditolak. Brand image has a significant effect on purchasing decisions for Wardah products for students in the Management study program at Dehasen University Bengkulu, this is evidenced by the results of the t test showing the tcount is greater than the ttable (8.976> 1.671) with a significant value of 0.000 <0.05, meaning that H0 is rejected and Had accepted. Product quality (X1), Price (X2), and Brand Image (X3) together have a significant effect on the decision to purchase (Y) Wardah products for students in the Management study program at Dehasen University Bengkulu, this is evidenced by the results of the F test showing Fcount> Ftabel (43.569> 2.76) with a significant value of 0.000.